2004
DOI: 10.1016/j.clpt.2004.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of human carboxylesterase 2, an enzyme involved in the activation of irinotecan into SN-38

Abstract: The hCE2 gene presents several polymorphisms, none of which seems to be involved in significant variations in protein activity and, therefore, in irinotecan activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 17 publications
0
41
0
2
Order By: Relevance
“…NM_001025194 and NM_003869, respectively). Recently, numerous single nucleotide polymorphisms have been identified in hCE-1 and hCE-2 [16][17][18]. So far, none of these polymorphisms have been shown to directly affect esterase activity or expression, and the variability in carboxylesterase activity is thought to be more likely of environmental rather than genetic origin [18].…”
Section: Preparation Of Recombinant Human Carboxylesterasesmentioning
confidence: 99%
See 1 more Smart Citation
“…NM_001025194 and NM_003869, respectively). Recently, numerous single nucleotide polymorphisms have been identified in hCE-1 and hCE-2 [16][17][18]. So far, none of these polymorphisms have been shown to directly affect esterase activity or expression, and the variability in carboxylesterase activity is thought to be more likely of environmental rather than genetic origin [18].…”
Section: Preparation Of Recombinant Human Carboxylesterasesmentioning
confidence: 99%
“…Recently, numerous single nucleotide polymorphisms have been identified in hCE-1 and hCE-2 [16][17][18]. So far, none of these polymorphisms have been shown to directly affect esterase activity or expression, and the variability in carboxylesterase activity is thought to be more likely of environmental rather than genetic origin [18]. Although the existence of these types of polymorphisms in hCE-1 and hCE-2 are not unexpected, the relative roles that these polymorphisms play in the metabolism of xenobiotics such as pyrethroids and prodrugs are still unclear.…”
mentioning
confidence: 99%
“…This result might be caused by genetic polymorphisms, such as single nucleotide polymorphisms (SNPs) in the CES2 gene. Several SNPs and haplotypes have been reported for the CES2 gene (Charasson et al, 2004;Marsh et al, 2004;Wu et al, 2004), and large ethnic differences in CES2 SNP frequencies are found among Europeans, Africans, and Asian-Americans (Marsh et al, 2004).…”
mentioning
confidence: 99%
“…This result might be caused by genetic polymorphisms, such as single nucleotide polymorphisms (SNPs) in the CES2 gene. Several SNPs and haplotypes have been reported for the CES2 gene (Charasson et al, 2004;Marsh et al, 2004;Wu et al, 2004), and large ethnic differences in CES2 SNP frequencies are found among Europeans, Africans, and Asian-Americans (Marsh et al, 2004).Previously, 12 exons and their flanking regions of CES2 were sequenced from 153 Japanese subjects, who received irinotecan or steroidal drugs, and 12 novel SNPs, including the nonsynonymous SNP, 100CϾT (Arg 34 Trp), and the SNP at the splice acceptor site of intron 8 (IVS8-2AϾG) were found (Kim et al, 2003). In vitro functional characterization of these SNPs and an additional nonsynonymous SNP, 424GϾA (Val 142 Met), suggested that the 34 Trp and 142 Met variants were defective, and that IVS8-2G might be a lowactivity allele (Kubo et al, 2005).…”
mentioning
confidence: 99%
“…Irinotecan is a prodrug that has been widely used in the treatment of advanced cancers and is activated by human carboxylesterase 2. Although its gene presents several polymorphisms and an intronic SNP is found to be associated with reduced carboxylesterase 2 mRNA expression in colorectal tumor , none of the variations in the carboxylesterase 2 gene are found to be associated with protein activity (Charasson et al 2004). Similarly, the polymorphism in the histamine-N-methyltransferase gene is not associated with gastric ulcer ).…”
Section: Genomic Variation and Drug Metabolizing Genesmentioning
confidence: 99%